Network democracy : conservative politics and the violence of the liberal age - Giesbrecht, Jared, 1979- (McGill-Queen's University Press, 2017)
A unique hybrid of ancient and contemporary conservative thought that offers a radical challenge to Western liberalism.
Keywords: Democracy.; Conservatism.; Liberalism.; Violence.; Time pressure.; Free enterprise.; Violence; Conservatisme.; Libéralisme.; Contrainte de temps.; conservatism.; liberalism.; violence.; POLITICAL SCIENCE -- General.; Free enterprise; Conservatism; Democracy; Liberalism; Time pressure